2008
DOI: 10.1089/jmf.2007.591
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Suppresses Cisplatin-Induced Apoptosis in Auditory Cells: Possible Mediation Through Induction of Heme Oxygenase-1 Expression

Abstract: Luteolin has been shown to possess antitumorigenic, antioxidant, and anti-inflammatory properties. In the present study, we investigated the protective mechanism of luteolin against cisplatin-induced apoptosis in auditory (House Ear Institute-Organ of Corti 1 [HEI-OC1]) cells. Luteolin was found to induce the expression of heme oxygenase-1 (HO-1) in a dose- and time-dependent manner. Luteolin also activated the extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase pathway, which plays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Similar up-regulation of HO-1 production occurs in the presence of curcumin (37), chalcone (38) and naringenin-7-O-glucoside (39). In a previous study, we also found that piperine protects cells against cisplatin-induced apoptosis by up-regulating the expression of anti-oxidative genes through the Nrf2 transcription factor pathway (31).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar up-regulation of HO-1 production occurs in the presence of curcumin (37), chalcone (38) and naringenin-7-O-glucoside (39). In a previous study, we also found that piperine protects cells against cisplatin-induced apoptosis by up-regulating the expression of anti-oxidative genes through the Nrf2 transcription factor pathway (31).…”
Section: Discussionsupporting
confidence: 68%
“…Epicatechin can also inhibit cisplatin-induced apoptosis and intracellular ROS generation (30). In addition, the activity of HO-1 can suppress the apoptotic effect of cisplatin (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CoPPIX inhibits cisplatin-induced death in the HEI-OC1 auditory-derived cell line (Kim et al 2006a(Kim et al , 2009So et al 2006So et al , 2008Choi et al 2007Choi et al , 2008Choi et al , 2011Gao et al 2010). HO-1 expression has been reported in cochlear hair cells and stria vascularis following a variety of stressors, including noise stress, heat stress, and pharmacological induction (Fairfield et al 2004;Lopez et al 2008;Kim et al 2009;Matsunobu et al 2009;Fetoni et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological induction of HO-1 is protective against multiple stresses in many tissue types, including ischemia-reperfusion injury in liver and retina (Tsuchihashi et al 2007;Sun et al 2010). Several studies have demonstrated that inducers of HO-1 protect against cisplatin-induced death in the HEI-OC1 auditory cell line (Kim et al 2006a(Kim et al , 2009So et al 2006So et al , 2008Choi et al 2007Choi et al , 2008Choi et al , 2011Gao et al 2010). We have shown that HO-1 induction inhibits hearing loss and hair cell death caused by aminoglycoside antibiotics (Francis et al 2011).…”
Section: Introductionmentioning
confidence: 99%